Genome-wide identification and molecular evolution of NAC gene family in Dendrobium nobile - Fu, Chun; Liu, MingYu (Frontiers in Plant Science, 2023)
Based on genome data of Dendrobium nobile, the NAC gene family was identified and analyzed by bioinformatics methods. In this study, we identified 85 NAC genes in Dendrobium nobile genome, and systematically analyzed the NAC gene family. We found that they were distributed unevenly in the nineteen chromosomes. The amino acid length of D. nobile NAC gene family (DnoNACs) ranged from 80 to 1065, molecular weight ranged from 22.17 to 119.02 kD, and isoelectric point ranged from 4.61~9.26. Its promoter region contains multiple stress responsive elements, including light responsive, gibberellin-responsive, abscisic acid responsiveness, MeJA-responsiveness and drought-inducibility elements. Phylogenetic analysis indicate that the D. nobile NAC gene family is most closely related to Dendrobium catenatum and Dendrobium chrysotoxum. Analysis of SSR loci indicates that the fraction of mononucleotide repeats was the largest, as was the frequency of A/T. Non-coding RNA analysis showed that these 85 NAC genes contain 397 miRNAs. The collinearity analysis shows that 9 collinear locis were found on the chromosomes of D. nobile with Arabidopsis thaliana, and 75 collinear locis with D.chrysotoxum. QRT-PCR experiment under different salt concentration and temperature conditions verified the response mechanism of DnoNAC gene family under stress conditions. Most DnoNAC genes are sensitive to salt stress and temperature stress. The results of this study provide a reference for further understanding the function of NAC gene in D. nobile. Keyword：Dendrobium nobile，NAC gene family，Genome-wide indentification；Molecular evolution；Collinearity analysis